Primary postpartum hemorrhage and associated factors among delivering women in Gedeo Zone, Southern Ethiopia - Zenebe, Getachew Assefa; Zenebe, Wagaye Alemu; Ewunie, Temesgen Muche; Dires, Selamawit (Frontiers in Medicine, 2023)
Introduction Primary postpartum hemorrhage is still the main cause of maternal death worldwide, especially in low-resource nations like Ethiopia where there are insufficient healthcare facilities and a shortage of skilled medical personnel. Data on the prevalence of primary postpartum hemorrhage in the study population are scarce or non-existent. Objective The aim of this study was to assess the prevalence of primary postpartum hemorrhage and its associated factors among delivering women in Gedeo Zone, Southern Ethiopia, in 2021. Methods A facility-based cross-sectional study was carried out from January 1 to March 30, 2021, in public health facilities in the Gedeo Zone. A randomly selected 577 participants were involved in the study. Data were gathered using an interview-administered, pre-tested, structured questionnaire. The gathered information was imported into Epi Info 3.5.1 and analyzed with SPSS 23. Descriptive data was presented using tables and graphs. A logistic regression model was fitted. A bivariable and multivariable logistic regression model was computed to identify the presence and strength of association. To run multivariable logistic regression analyses, variables with P-values of <0.2 were used. The odds ratio, a 95% confidence interval (CI), and a P-value of <0.05 were used to identify variables that were associated with primary postpartum hemorrhage. Results The magnitude of primary postpartum hemorrhage was 4.2% (95% CI: 2.4–6.0). Postpartum hemorrhage was significantly associated with current antepartum hemorrhage (AOR = 11.67; 95%CI: 7.17–16.17), twin delivery (AOR = 6.59, 95%CI: 1.48–11.70), uterine atony (AOR = 8.45, 95%CI: 4.35–12.55), and prolonged labor (AOR = 5.6, 95%CI: 2.9–8.50). Conclusions The prevalence of primary postpartum hemorrhages in the Gedeo Zone, Southern Ethiopia was 4.2%. Current ante partum hemorrhage, twin delivery, uterine atony, and prolonged labor were predictors of primary postpartum hemorrhage. The results back up the necessity for care in the early postpartum period so that clinicians may quickly identify any issues, prevent and start treating excessive blood loss early, and, taking into account the aforementioned factors, possibly reduce the frequency of primary postpartum hemorrhage.